Syphilis intervention in pregnancy: Zambian demonstration project. Issue 3 (June 1990) - Hira, S K; Bhat, G J; Chikamata, D M; Nkowane, B; Tembo, G; Perine, P L; Meheus, A
Abstract : Despite availability of simpler serologic tests for syphilis and near cure with penicillin, unacceptably high prevalence of infectious maternal syphilis exist in many developing countries, including Zambia. It is the foremost risk factor for mid-trimester abortions, stillbirths, prematurity and morbidity and mortality among infants born with congenital syphilis in Zambia. An intervention project was conducted in Lusaka aimed at demonstrating the effectiveness of new health education methods and prenatal screening for syphilis in reducing the adverse outcomes during pregnancy. During pre-intervention phase, approximately 150 consecutive pregnant women from each of the three study and the three control centres were recruited when they presented in labour at the University Teaching Hospital. The intervention phase lasted for one year at the three study centres during which new methods of health education were introduced to improve early attendances during pregnancy. Also, on-site syphilis screening was performed twice during pregnancy and seroreactive women, and in many cases their sexual partners, were treated by the existing prenatal clinic staff. During the post-intervention phase the steps of pre-intervention phase were repeated to evaluate the impact of intervention. Overall, 8.0% of women were confirmed seroreactive for syphilis; there was no difference between the study and the control centres (p greater than 0.05). Fifty seven percent (132/230) of syphilitic pregnancies ended with an adverse outcome, that is, abortion (RR 5.0), stillbirth (RR 3.6), prematurity (RR 2.6) and low birth weight (RR 7.8). The overall risk of adverse outcomes due to syphilis was 8.29 (95% confidence interval 6.53, 10.53). The new methods of health education were effective and the percentage of women who had their first prenatal visit under 16 weeks of gestation improved from 9.4 to 42.5. Although screening and treatment during intervention was suboptimal, the adverse outcomes attributable to syphilis were reduced to 28.3%; this is almost a two-third reduction when compared with 72.4% of adverse outcomes at control centres (p < less than 0.001). The intervention is culturally and politically acceptable in Zambia. The cost of each prenatal screening is US$0.60 and of averting each adverse outcome US$12. In countries with high rates of syphilis, there is an urgent need for STD control and Maternal and Child Health (MCH) programmes to pool their resources together to revitalise the prenatal care.